(3fXQjGJ heSGFd aj GdLHQ GdNWjs - (3djHTJQ(B, (3SjehQs ((3GdbGgQI(B:s (3GdOGQ GdOhdjI ddfTQhGdJhRjY(B,s, 1999)
(3GdJLgGJ aj GdaQGZ (BR (3GdaQGZ (BC -(3GdeYGOdGJ GdNWjI(B- (3GdeUahaGJ(B- (3GdaQGZGJ GdeJLgI hGdaQGZGJ GdLRFjI(B- (3GdGSGS hGdHYO(B- (3GdJTcjdGJ(B( (3GdQhGSe(B) (3GdNWjI(B- (3GdeUahaGJ hGdeDKQGJ GdNWjI(B- (3GdeMOOGJ(B- (3Gdbje GdPGJjI(B- (3GdeJLgGJ GdPGJjI (B- (3GdUjZ GdbGfhfjI (B- (3GdEQJHGW GdOGdj GdNWj hGdaQGZ GdKfGFj(B- (3GdCTcGd GdKfGFjI(B- (3GdJQHjYjI hGdehGabI dfaSgG(B- (3aQGZGJ MGUd GdVQH GdbjGSj(B.s
Keywords: (3GdLHQs; (3GdQjGVjGJs